1994
DOI: 10.1159/000126806
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Delta-Sleep and Plasma Delta-Sleep-Inducing Peptide in Patients with Cushing Syndrome

Abstract: To evaluate the sleep disturbances of patients with Cushing syndrome and to examine the relationship between the sleep disturbances and plasma levels of delta-sleep-inducing peptide-like immunoreactivity (DSIP-LI), we performed three polysomnographic/endocrinological studies in patients with Cushing syndrome. In study 1, polysomnography was studied in 12 patients and 12 matched normal volunteers. In addition, DSIP-LI was measured every 30 min for 24 h in 9 patients with Cushing syndrome and 12 normal volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The REM latency in normal individuals is around 103 min (34). Moreover, the absence of HC resulted in a decrease in sleep continuity, while HC replacement resulted in a more consolidated sleep pattern.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…The REM latency in normal individuals is around 103 min (34). Moreover, the absence of HC resulted in a decrease in sleep continuity, while HC replacement resulted in a more consolidated sleep pattern.…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Because these disorders are associated with high levels of cortisol, it follows that SWS should be diminished in the sleep of these patients. Indeed, Friedman et al (1994) demonstrated that patients with Cushing's syndrome spent much less time in SWS than did healthy controls. REM sleep, however, was not significantly different between groups in this study.…”
Section: The Role Of Cortisolmentioning
confidence: 99%
“…In the pituitary of vertebrates DSIP‐LI co‐localizes with such peptides as corticotrophin‐like intermediate lobe peptide (CLIP), adrenocorticotropic hormone (ACTH), melanocyte‐stimulating hormone (MSH), thyreotropic hormone (TSH) and melanin‐concentrating hormone (MCH), and it co‐localizes with adrenaline and noradrenaline in the adrenal medulla (Table 2). The human pituitary does not appear to be the site of synthesis of plasma DSIP‐LI (Friedman et al . 1994a).…”
Section: Structure Of Delta Sleep‐inducing Peptide (Dsip) and Dermorpmentioning
confidence: 99%